2017
DOI: 10.1515/jcim-2016-0154
|View full text |Cite
|
Sign up to set email alerts
|

An innovative mindfulness and educational care approach in an adult patient affected by gastroesophageal reflux: the IARA model

Abstract: Patients affected by gastroesophageal reflux disease (GERD) have a poor quality of life caused by several manifestations such as cough, asthma, laryngitis and dental erosion. The clinical conditions are highly disabling for patients and symptoms are difficult to manage. These conditions lead to many discomforts which contribute to an increase of the disease perception. For these reasons, it is important to improve the interventions on psychological aspects that ameliorate the patients' quality of life. The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Therefore, Yoga, in addition to intervening on the back disuse, may have an antianxiety effect decreasing pain 41 . Furthermore, it has been proven that people, when educating and informing about their disease, improve their psycho-physical conditions 42,43 also by reducing anxiety and depres- 45 have evaluated and confirmed the effectiveness of neuroscience education for pain, disability, anxiety, and stress in chronic musculoskeletal pain. The Back school treatment is based on education in regard to back.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, Yoga, in addition to intervening on the back disuse, may have an antianxiety effect decreasing pain 41 . Furthermore, it has been proven that people, when educating and informing about their disease, improve their psycho-physical conditions 42,43 also by reducing anxiety and depres- 45 have evaluated and confirmed the effectiveness of neuroscience education for pain, disability, anxiety, and stress in chronic musculoskeletal pain. The Back school treatment is based on education in regard to back.…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, this umpteenth “black swan” brought about by a virus once again makes us aware of the importance of education in emotional regulation. Knowing how to manage emotions well, for example, through mindfulness practices – which can increase well-being and decrease anxiety and depression in healthy, professionals and patient populations ( De Giorgio et al, 2017a , b ; Grazzi et al, 2017 ; Padovan et al, 2018 ; Ramaci et al, 2020b ) – can allow people to have a balanced reaction and a clearer understanding of the phenomenon, thanks also to the neuro-bio-physiological effects that these practices have on the brain. In fact, it has been widely proven in the literature that these types of practices are able to structurally and functionally modify the areas of the brain that regulate the networks related to emotions (see for review, Young et al, 2019 ) and even reduce the size of the amygdala ( Taren et al, 2013 ).…”
mentioning
confidence: 99%
“…It has also been shown that mindfulness meditation training raises awareness of the interoceptive signals coming from the body (Farb et al, 2013 ) reducing anxiety, distress and even depression (Goldin and Gross, 2010 ; Gallego et al, 2015 ; Zhang et al, 2015 ; Crowe et al, 2016 ) improving the QoL (Grazzi et al, 2017 ). It also has been demonstrated both this mind-body shift increases the interoceptive attention awareness (Critchley et al, 2004 ; Farb et al, 2013 ; Kerr et al, 2013 ) and GI exercise has neural foundations (Kosslyn et al, 2001 ) useful also in emotional disorders (Holmes and Mathews, 2010 ), in management of symptoms in patients receiving chemotherapy (Charalambous et al, 2016 ), and among patients with inflammatory bowel disease (Mizrahi et al, 2012 ; De Giorgio et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This model was already used on chronic tension-type headache (Gulotta et al, 2015 ) and gastroesophageal reflux (De Giorgio et al, 2017 ) with encouraging results particularly toward emotion management (De Giorgio, 2016 ).…”
Section: Introductionmentioning
confidence: 99%